2021
DOI: 10.3389/fendo.2021.798577
|View full text |Cite
|
Sign up to set email alerts
|

MnFtz-f1 Is Required for Molting and Ovulation of the Oriental River Prawn Macrobrachium nipponense

Abstract: Molting and ovulation are the basic processes responsible for the growth and reproduction of Macrobrachium nipponense; however, the molecular mechanisms of molting and ovulation in M. nipponense are poorly understood. The present study aimed to use MnFtz-f1 as the starting point to study the molting and ovulation phenomena in M. nipponense at the molecular level. The full-length MnFtz-f1 cDNA sequence was 2,198 base pairs (bp) in length with an open reading frame of 1,899 bp encoding 632 amino acids. Quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 81 publications
4
18
0
Order By: Relevance
“…The RT‐qPCR results showed that CqFtz‐f1 abundances gradually increased from Stage I to IV, and reached peak level at mature ovary. This finding was consistent with results from studies performed in other crustaceans (Li, Li, Wen, et al, 2012; Yuan et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The RT‐qPCR results showed that CqFtz‐f1 abundances gradually increased from Stage I to IV, and reached peak level at mature ovary. This finding was consistent with results from studies performed in other crustaceans (Li, Li, Wen, et al, 2012; Yuan et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…It was noted that staging based on ovarian morphology and histology was considered to be more appropriate (Wang et al, 2020). This finding was consistent with results from studies performed in other crustaceans (Li, Li, Wen, et al, 2012;Yuan et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations